FRP Strengthened Concrete Beams Subjected to Drop Weight Impact and Static Loading - Eriksson, Edvard; Gustafsson, Viktor (My University, 2021)
Concrete is a material that is commonly used in protective structures, e.g. civil defence shelter and fortifying facilities. The structural response in these types of structures when subjected to impulse loading is highly interesting. The aim of this project is to increase the knowledge of the structural response of impulse loaded reinforced concrete (RC) structures strengthened with fibre reinforced polymer (FRP) through an experimental study. Focus on this thesis is on the effect FRP strengthening has on impact loaded structures when it comes to deformation capacity, ultimate load capacity and energy absorption. A literature study was conducted regarding impulse loaded structures, FRP in general and FRP strengthening of RC structures in particular. Different strengthening methods and how to achieve a good adhesion between concrete and FRP were of interest. The experimental study consisted of drop weight tests from 3.0, 4.0, 5.0 and 5.7 m followed by static loading until failure for unstrengthened and FRP strengthened beams with two types of adhesives. To complement, beams were tested statically only to act as references. High speed cameras were used to capture the response during the tests, one capturing the beam and one capturing the drop weight. The data was later processed using Digital Image Correlation (DIC). Material tests of concrete, reinforcement and the adhesives were also conducted. FRP proved to give an enhanced structural response compared to unstrengthened beams. The results showed that FRP strengthened beams obtained a higher load carrying capacity, a larger deformation capacity and a good energy absorption. In order to achieve a good adhesion between concrete and FRP, response, a well-treated surface was found to be crucial.
Keywords: Reinforced concrete, Fibre reinforced polymer, FRP strengthening; Impulse loading, Drop weight test, FRP debonding, Residual strength; Energy absorption, Plastic rotation capacity